2009
DOI: 10.1002/dc.21089
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration biopsy cytomorphology of primary pulmonary germ cell tumor metastatic to the brain

Abstract: Extragonadal germ cell tumors are uncommon and such tumors originating from the lung parenchyma are extremely rare. This is a case of 68-year-old female who was admitted with complaints of right-sided weakness, inability to maintain her balance, right-sided headache, and bloody sputum. Her workup revealed two enhancing brain lesions and large lung mass involving the left lower lobe. Fine-needle aspiration (FNA) of the lung followed by craniotomy was performed and the patient was initially diagnosed with lung a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Both may have similar cellular arrangements and similar cytomorphology. Both can show a background of tumor necrosis, as in our case [9].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Both may have similar cellular arrangements and similar cytomorphology. Both can show a background of tumor necrosis, as in our case [9].…”
Section: Discussionmentioning
confidence: 52%
“…In the same year, Vaideeswar et al reported seven cases of PPC seen in autopsy and surgical materials [8]. Four additional cases were found in a review by Arabi and collegues [9]. In our review of the literature to date, we found four additional cases of PPC [10].…”
Section: Discussionmentioning
confidence: 66%
“…JEG-3 tumors grew the fastest and reached ~1500 mm 3 in volume in 15 days compared to ~19 and 26 days for JAR and BeWo tumors respectively (Fig. 3A).…”
Section: Resultsmentioning
confidence: 96%
“…The increase in median survival of mice bearing the JEG-3 xenograft was modest with a median survival of 22 days for the control group and 27 days for the sFLT01 treatment group. sFLT01 (25 mg/kg) was more active in the JAR model resulting in 18 days of tumor growth delay determined when the mean tumor volumes reached ~1000 mm 3 (Fig. 6B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation